CLIMATE CHANGE RISKS, AGRICULTURAL PRODUCTION, AND THE ROLE OF INSURANCE - Njegomir, Vladimir; Pejanović, Radovan; Maksimović, Goran (Economics of Agriculture, 2016)
Climate change in the form of global warming is visible, tangible, measurable and is one of the most signifcant risks facing the world. During the conceptualization as the objective of the paper, we have determined the analysis of the impact of climate change on agricultural production and the ways of reduction of negative impacts. The most important results of the present work are the analysis of the implications of climate change on agricultural production and food security, adaptation possibilities of agriculture and the role of agriculture insurance. The main conclusions are that climate change negatively affects agricultural production and food security, especially in subtropical areas while there is limited potential for a positive impact of climate change in the northern hemisphere. There are two possible choices for agricultural producers, under the implications of climate change, that are not necessarily mutually exclusive: 1) fnding a long term sustainable solution based on the adaptation and 2) obtaining insurance coverage.